Debt Projections and Fiscal Sustainability with Feedback Effects - John Creedy; Grant Scobie (New Zealand Government, The Treasury, 2015)
This paper analyses long-term fiscal sustainability with a model which incorporates a number of feedback effects. When fiscal policy responds to ensure long-term sustainability, these feedback effects can potentially modify the intended outcomes by either enhancing or dampening the results of the policy interventions. The feedbacks include the effect on labour supply in response to changes in tax rates, changes in the country risk premium in response to higher public debt ratios, and endogenous changes in the rate of productivity growth and savings that respond to interest rates. A model of government revenue, expenditure and public debt which incorporates these feedbacks is used to simulate the outcome of a range of fiscal policy responses. In addition the effects of population ageing and productivity growth are explored.
Keywords: E62; 330; Finanzpolitik; Nachhaltigkeit; Öffentliche Einnahmen; Öffentliche Ausgaben; Wirtschaftsindikator; Wirtschaftsmodell; Neuseeland